Principles of Green Banking Managing Environmental Risk and Sustainability - Barua, Suborna (The Moorad Choudhry Global Banking Series, 2020)
Environmental sustainability is perhaps the key societal challenge of our times. Achieving it will require a significant level of financing and investment, and here the role of the banking industry is fundamental. Banks can play a broader and far-reaching role by adopting environmental concerns in their internal and external business operations. Principles of Green Banking is a comprehensive account of the different aspects of green banking and offers theories and principles as well as practical how-to guidelines to adopt green banking practices. This book discusses why green banking is central to achieving sustainable development. It illustrates the evolution of green banking around the world, different types of environmental risks created by firms and how these risks offer threats to sustain ability, and ongoing trends and patterns of green banking practice. Critically, it also presents an outline of the regulatory framework necessary to help the entire banking sector adapt to the change towards green banking. It is a valuable resource for financial sector professionals and scholars in the fields of sustainable finance and banking.